Welfare magnets : a new case for a national standard - Peterson, Paul E. (Brookings Institution, 1990)
""The best way of handling the question of how much to give the poor, politicians have discovered, is to avoid doing anything about it at all,"" note Paul Peterson and Mark Rom. The issue of the minimum people need in order to live decently is so difficult that Congress has left this crucial question to the states--even though the federal government foots three-fourths of the bill for about 15 million Americans who receive cash and food stamp benefits. The states differ widely in their assessment of what a family needs to meet a reasonable standard of living, and the interstate differences in.